The biological control of Egeria densa Planch. (Hydrocharitaceae) in South Africa - Smith, Rosali (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Over the last thirty years, biological control, the use of host-specific natural enemies, has been a huge asset in the management exotic aquatic macrophytes such as Pistia stratiotes L. (Araceae), Pontederia crassipes Mart. (Solms) (Pontederiaceae), Azolla filiculoides Lam. (Azollaceae), Salvinia molesta D.S. Mitch (Salviniaceae) and Myriophyllum aquaticum (Vell.) Verdc. (Haloragaceae), also known as the "Big Bad Five" in South Africa. Despite these successes, freshwater ecosystems in South Africa have been harder to restore to an invasive macrophyte-free space, due to chronic disturbances such eutrophication, propagule dispersal and hydrological alterations. In the Anthropocene, where human activities have profound effects on their environment, these disturbances weakens ecological resilience and drive aquatic plant invasions. Due to long periods of invasions and the presence of a new suite of exotic aquatic plant propagules, native vegetation recolonization has been slow or even absent. Instead, the release of resources, such as sunlight, nutrient and space through aquatic weed management acts as a catalyst for secondary biological invasion. New invasive aquatic weeds include submerged and rooted emergent growth types, with Egeria densa Planch. (Hydrocharitaceae) the most widely distributed submerged aquatic weed in South Africa. It can quickly form dense monoculture stands that have ecological, economic and social impacts. Because of its ability to regenerate from plant fragments with double nodes, mechanical control is inappropriate. Additionally, mechanical and chemical control not only affects E. densa but have significant non-target effects. In response to its rapid spread over the last 20 years, especially following floating invasive aquatic management, a biological control programme was initiated, and in 2018, the leaf-mining fly, Hydrellia egeriae Rodrigues (Diptera: Ephydridae) was released. This was the first release of a biological control agent against E. densa in the world, and the first agent released against a submerged aquatic weed in South Africa. This thesis comprises the subsequent step of a biological control program when permission for the release of an agent have been obtained. A brief history of macrophyte invasions in South Africa's unique freshwater systems are given in the literature review. Contributing factors to secondary invasions within the context of ecological resilience are introduced. An argument for the benefit of biological control as nuisance control is given, especially because E. densa and its natural enemy, H. egeriae is the focus species of this thesis. The main goal after permission for the release of an agent have been obtained, is to establish and build-up field populations. Research questions in this thesis aimed to investigate factors that contribute to or negate this goal. Through laboratory and field experiments we investigated the thermal physiology of the agent, and its climatic suitability to its novel range; different release strategies on field establishment and biotic resistance through the acquisition of novel parasitoids. Considering the longevity of this biological control program, we investigated the effects of elevated CO2 on the interaction between E. densa and H. egeriae through open top chamber experiments. Laboratory thermal physiology results showed that the agent is able to survive, develop and proliferate at all E. densa sites throughout the year. This is confirmed with the establishment of the agent at two release sites, the Nahoon River in the Eastern Cape Province and the Midmar Dam in KwaZulu-Natal. Post-release surveys showed that H. egeriae requires augmentative releases to sustain field populations. Without augmentative releases, H. egeriae herbivory levels were almost negligent. However, a contributing factor to low field-populations was parasitism. The biological control agent acquired three parasitoids, which have previously been described from Hydrellia lagarosiphon Deeming (Diptera: Ephydridae), a specific herbivore to Lagarosiphon major (Ridl.) Moss (Hydrocharitaceae). These results provide information on the immediate establishment and effectiveness of the H. egeriae. Results from the elevated CO2 study suggest that E. densa will become less nutritious through a shift in leaf C/N ratio, when ambient 800ppm is bubbled into experimental growth chambers. Hydrellia egeriae feeding was affected by ambient CO2 levels and plant nutrient availability. The set levels of ambient CO2 levels used in this experiment produced dissolved inorganic carbon levels that were lower than dissolved inorganic carbon levels in E. densa invaded sites. This suggests that, submerged aquatic plant-insect interactions may be harder to predict from only laboratory experiments. Further investigations are necessary to establish system-specific characteristics i.e. dissolved inorganic carbon and target plant nutritional quality. The biological control of E. densa in South Africa is still in its infancy. This study presents results from post-release surveys up until two years after the agent was released. From this study, Hydrellia egeriae exhibits the potential to be an effective biological control agent, but release strategies should be adapted to sustain field populations and to limit field parasitism effects. Continued post-release surveys will provide a more comprehensive idea of the seasonal fluctuations of field-populations and parasitism. Surveys at multiple sites will provide information on potential site specific characteristics that contribute to or negate biological effort. Considering the high nutrient status of South African freshwater systems, a more holistic approach to E. densa management is necessary. This will require the strengthening of ecological resilience to prevent systems from shifting into an alternate invasive stable state. In addition, aquatic weed management needs to be addressed by a resilient social network, which ultimately calls for the strengthening of socio-ecological resilience.
Keywords: Egeria (Plant genus) Biological control -- South Africa; Hydrocharitaceae Biological control -- South Africa; Aquatic weeds Biological control -- South Africa; Leafminers -- South Africa; Plant invasions -- South Africa; Resilience (Ecology) -- South Africa; Freshwater ecology -- South Africa; Hydrellia -- South Africa; Submerged macrophyte